Investment in English pronunciation learning: a multiple case study of English major students in mainland China - Zhang, Yan Mei; Shanina Sharatol Ahmad Shah,; Fatiha Senom, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Learning English has a significant positive impact on China's growth, especially in light of the country's recent three decades of reform and opening-up policies. The standard for Chinese students' English pronunciation to be comprehensible is higher since English pronunciation is crucial for communication. However, English pronunciation is still a challenge for English major students. This article reports on multiple case studies of three Chinese English major students’ lived experiences of English pronunciation investments across different contexts, including inside and outside the classroom. The study adopts a qualitative research approach where multiple data sources such as semi-structured in-depth interviews with the participants; classroom observations, diaries, and documents, yielded thick descriptions of participants’ English pronunciation learning. The interview data was transcribed and then analyzed using N-Vivo 12. The results showed that students with varying levels of English pronunciation competency held two different opinions about English pronunciation, influencing their varied investments in English pronunciation in various circumstances. Norton's concept of investment informed these conclusions. Meanwhile, personal agency responding to particular contextual situations also impacts their strategic L2 investments. This article calls for the importance of a holistic understanding of students’ English pronunciation learning in and out of the classroom for an in-depth understanding of the complexities of learners varied English pronunciation investments.